Pengaruh Social Commerce di Media Sosial terhadap Persepsi Publik pada Pelanggan MS Glow di Pasuruan - Maulida Rahmanita Putri; Yasmin Kamila; Wardah Laily; Audita Sandra Dinata; Agung Candra Wahyudi; Muhammad Abdullah (JURNAL ADMINISTRASI KANTOR, 2025)
This research seeks to assess how much social commerce activities affect public views on MS Glow products in the Pasuruan area. Progress in digital technology has positioned social commerce as an essential strategy for MS Glow to establish its brand image and boost consumer confidence via reviews, content sharing, and engagements on social media sites. The research employs a quantitative method, involving an online survey of 105 participants chosen by purposive sampling, with data processed through simple linear regression. The results reveal that social commerce exerts a positive and meaningful influence on public perception, featuring a notably strong relationship. However, inconsistencies persist in public views due to discrepancies between promotional materials and actual user experiences, along with slow replies from the brand. As a result, MS Glow is advised to enhance the standard and uniformity of promotional content and speed up responses in online interactions. Keywords: Social Commerce, Public Perception, MS Glow, Social Media, Brand Image.